A STUDY ON DIFFERENT COMPOSITE MATERIAL SYNTHESIS CHARACTERIZATION AND APPLICATION FOR THE REMOVAL OF WATER POLLUTANT BY USING ADSORPTION - Awadhesh Kumar; Dr. Anil Sharma (The Bioscan, 2024)
Water pollution remains one of the most critical global environmental challenges, with rising contamination from industrial, agricultural, and domestic activities. Traditional water treatment methods often fall short in addressing the diverse range of pollutants, highlighting the need for innovative solutions. Composite materials have emerged as a promising approach to enhance the efficiency of pollutant removal, owing to their versatile properties and ability to be tailored for specific contaminants. This review explores various types of composite materials, including organic-inorganic composites, polymer-based composites, carbon-based composites (such as graphene oxide and biochar), and metal-organic frameworks (MOFs), focusing on their synthesis, characterization, and application in water treatment. The adsorption process, particularly through the use of these composite materials, is examined as an effective method for removing heavy metals, organic pollutants, and dyes from contaminated water. Key characterization techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and BET surface area analysis are discussed to highlight the structure-property relationships of these composites. Furthermore, adsorption isotherms and the effect of environmental conditions, including pH, on the performance of composites are analyzed. The review underscores the potential of composite materials to address the challenges of water purification, while also identifying areas for future research, including material regeneration and large-scale application. The integration of interdisciplinary approaches is emphasized to drive further advancements in the development of cost-effective, efficient, and sustainable water treatment technologies.